Problematizations about distance education in contemporaneity from the Heideggerian perspective: Beyond the debate on distances and proximity - Ramos , Viviane Kate Pereira; Landim , Ossian Soares (Seven Editora, 2023)
This paper aims to analyze the issue of Distance Learning (EaD), through the perspective of two categories: distance and proximity. From such reflections, we intend to raise notes that make it possible to understand how the confrontation between face-to-face and non-face-to-face teaching (EaD) occurs, discussing to what extent this issue is an analytical contradiction. To this end, a literature review was carried out, dialoguing with the conception of the philosopher Martin Heidegger about proximity and distance, in order to problematize the debate beyond the question about metrage. About the distance education education, we highlight the contributions brought by Amaral Filho; in addition to dialoguing with authors such as Paulo Freire, based on the concepts of liberating education and pedagogy of autonomy; and the philosopher and sociologist Pierre Levy, through his important contributions to thinking about the science of information and communication in contemporary times. The initial reflections, brought in the present work, seek to contribute to broaden the discussions about face-to-face and distance learning in the contemporary context where education needs to (re)invent itself in a pandemic context. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-043